Coseismic deformation and source model of the 12 November 2017 MW 7.3 Kermanshah Earthquake (Iran–Iraq border) investigated through DInSAR measurements. Issue 2 (17th January 2019) - Kuang, Jianming; Ge, Linlin; Metternicht, Graciela Isabel; Ng, Alex Hay-Man; Wang, Hua; Zare, Mehdi; Kamranzad, Farnaz
ABSTRACT: A large earthquake with a magnitude of MW 7.3 struck the border of Iran and Iraq at the province of Kermanshah, Iran. In our study, coseismic deformation and source model of the 12 November 2017 Kermanshah Earthquake are investigated using ALOS-2 ScanSAR and Sentinel-1A/B TOPSAR Differential Interferometric Synthetic Aperture Radar (DInSAR) techniques. Geodetic inversion has been performed to constrain source parameters and invert slip distribution on the fault plane. The optimised source model from joint inversion shows a blind reverse fault with a relatively large right-lateral component, striking 353.5° NNW-SSE and dipping 16.3° NE. The maximum slip is up to 3.8 m at 12–14 km depth and the inferred seismic moment is 1.01 × 10 20  Nm, corresponding to MW 7.3, consistent with seismological solutions. The high-resolution optical images from SuperView-1 satellite suggest that most of the linear surface features mapped by DInSAR measurements are landslides or surface cracks triggered by the earthquake. Coulomb stress changes on the source fault indicating consistency between aftershock distribution and high loaded stress zones. Based on the stress change on neighbouring active faults around this area, the Kermanshah Earthquake has brought two segments of the Zagros Mountain Front Fault (MFF), MFF-1 and MFF-2, 0.5–3.1 MPa and 0.5–1.96 MPa closer to failure, respectively, suggesting the risk of future earthquakes. Recent major aftershocks (MW ≥ 5.0) could probably ease the seismic hazard on MFF-2, but the risk of earthquakes on MFF-2 is still increasing.